THE CUSTOMERS’ PERCEPTION TOWARD MARETING MIX OF HYPERMART, MULTI MART, AND FRESHMART MANADO - Manoppo, Vina Lenda (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Retailing is defined as all the activities that involve selling of goods or services directly to the final customer for their personal, non-business use via shops, market, door-to-door selling, and mail-order or over the internet where the buyer intends to consume the product. Retailing can also be defined as the activity that ensures that customers derive maximum value from the buying process. This research is conduct in Manado, North Sulawesi. The objectives of this research are to know the customers’ perception on marketing mix of retail store in Manado. This research is comparative study, which is a study conducted by collecting data from several settings or organizations. The population in this research are all current customers, buyers, and all potential customers, buyers and customers of  Hypermart, Multi Mart and Freshmart in Manado, whereas samples taken are 100 respondents. The conclusion of this research, people in manado have their own perception on retail store  (Hypermart, Multi Mart, and Freshmart). People in Manado see that each retail store have their own value to offer to their customer. This study reveals that in terms of product and place in marketing mix, Hypermart is more superior compare to both if it’s competitors. In the terms of price and promotion, Freshmart is more superior. This means Multi Mart’s marketing mix policy still in the shade of both of it’s competitors. Keywords: customer perception, retail store